Implementation of Law Number 20 Of 2023 As A Strengthening of the Implementation of the Functions and Authority of the Civil Service Based on Distributive Justice (Study by the BKPSDM of Mataram City) - Rudy Herlambang; Firzhal Arzhi Jiwantara; Siti Hasanah; Nurjannah Septyanun (Universitas Muhammadiyah Palu, 2026)
Law Number 20 of 2023 concerning State Civil Apparatus (ASN) is a new regulation that aims to transform state apparatus management through strengthening the merit system and applying the principle of distributive justice. This study aims to analyze the regulation of ASN functions and authorities, examine the implementation of ASN duties, and formulate an ideal concept for the implementation of ASN functions and authorities based on distributive justice within the BKPSDM of Mataram City. This study uses an empirical juridical method with a qualitative approach. Data was collected through interviews, observation, and documentation studies. The results of the study show that the implementation of Law Number 20 of 2023 has been running normatively, but has not been optimal in realizing distributive justice due to the limited number of ASN, workload imbalances, and the uneven distribution of career development and performance rewards. This study recommends strengthening the merit system, optimizing supervision, and establishing a bureaucratic culture oriented towards fairness and professionalism.